Avaliação de biodigestor com rejeito de queixada (Tayassu pecari) - Turnley, Stephanie [UNESP] (My University, 2019)
In view of the pollution that the human has caused to the environment with the inadequate disposal of tailings, animal feces can be used after biodigestion. Thus, this project aims to demonstrate, by means of biodigestor, a suitable destination when turning feces of Queixada (Tayassu pecari), in biofertilizer and with the future expectation of the use of biogas. The Queixada was used because it was of the same suborder of the pigs, which produce highly polluting wastes, and because of the availability and number of animals for the study. The project was carried out at the Wildlife Conservation Center in the municipality of Ilha Solteira, São Paulo, in the year 2018, where faeces and biofertilizer were evaluated chemically and microbiologically. The chemical analyzes were phosphorus, potassium, calcium, magnesium, sulfur, copper, iron, manganese and zinc. Microbiological analyzes evaluated fecal coliforms in feces and biofertilizer. The results demonstrated that the analyzes of chemical elements are compatible with studies with pig rejects, and with potential for use in perennial crops. In relation to fecal coliforms, a decrease in MPN of colonies was observed, suggesting that the process of biodigestion with the reject of jaw has potential for use and for new works.

Diante da poluição que o ser humano tem causado ao ambiente com o descarte inadequado de rejeitos, as fezes de animais podem ser utilizadas após a biodigestão. Assim, esse projeto tem o intuito de demonstrar, por meio de biodigestor, um destino adequado ao transformar fezes de Queixada (Tayassu pecari), em biofertilizante e com a expectativa futura da utilização do biogás. O Queixada foi utilizado por ser da mesma subordem dos suínos, os quais produzem dejetos altamente poluidores, e pelo fato da disponibilidade e número de animais para o estudo. O projeto foi realizado no Centro de Conservação da Fauna Silvestre no município de Ilha Solteira, São Paulo, no ano de 2018, onde as fezes e o biofertilizante foram avaliados química e microbiologicamente. As análises químicas realizadas foram fósforo, potássio, cálcio, magnésio, enxofre, cobre, ferro, manganês e zinco. As análises microbiológicas avaliaram coliformes fecais nas fezes e biofertilizante. Os resultados demonstraram que as análises de elementos químicos estão compatíveis com estudos com rejeitos de suínos, e com potencial para utilização em culturas perenes. Em relação aos coliformes fecais, uma diminuição no NMP de colônias foi observada, sugerindo que o processo de biodigestão com o rejeito de queixada possui potencial para utilização e para novos trabalhos.
Keywords: Biofertilizer; Disposal; Fecal coliforms; Waste; Biofertilizante; Coliformes fecais; Dejetos; Descarte